The effects of cooling vest intervention on physical, cognitive, and psychomotor vigilance performance in patients with multiple sclerosis: A pilot study - Burak, Mustafa; Burak, Sinem Erturan; Tatli, Sinan; Demir, Caner Feyzi (Elsevier, 2025)
[Abstract Not Available]
ISN World Congress of Nephrology (WCN) -- FEB 06-09, 2025 -- New Delhi, INDIA